The Unlikely Pilgrimage of Harold Fry : Harold Fry #1 - Joyce, Rachel (New York : Random House, 2012)
Harold Fry is convinced that he must deliver a letter to an old love in order to save her, meeting various characters along the way and reminiscing about the events of his past and people he has known, as he tries to find peace and acceptance.
Keywords: Walking -- Fiction; Men -- Great Britain -- Fiction; Walking -- Fiction; Men -- Great Britain -- Fiction; Great Britain -- Fiction; Great Britain -- Fiction